Sistem Cerdas Penilaian Ujian Essay Menggunakan Metode Cosine Similarity - Arifuddin, Muhammad Rizal; Ar Rafiq, Izzudin; Mubarok, Rifki; Susilo, Purnomo Hadi (Universitas Nusantara PGRI Kediri, 2023)
Technological developments have grown rapidly without exception in the world of education. The development of technology in the field of education can be seen by the number of information systems used for the learning process. The online learning process has many obstacles, especially when the exam is being conducted. Not all educators can conduct online exams by utilizing information technology. One of the most difficult exams is the essay exam. The essay exam that was conducted experienced many obstacles in terms of correcting and assigning grades to students. By utilizing intelligent information technology, this can be solved because everything can be done by the system automatically. This study aims to build an intelligent system for assessing essay exams using the cosine similarity method. In the system built, all the exam processes can be done automatically. The system can correct the answers written by students then the system will also automatically give a value according to the answers entered. The results of the study indicate that the system built can assist teachers in conducting online essay exams effectively and efficiently. This is because the system can correct students' answers by automatically matching the answers from the teacher.